KMT2C knockout generates ASD-like behaviors in mice - Brauer, Bastian; Merino-Veliz, Nicolas; Ahumada-Marchant, Constanza; Arriagada, Gloria; Bustos, Fernando J. (Frontiers in Cell and Developmental Biology, 2023)
Neurodevelopmental disorders have been associated with genetic mutations that affect cellular function, including chromatin regulation and epigenetic modifications. Recent studies in humans have identified mutations in KMT2C, an enzyme responsible for modifying histone tails and depositing H3K4me1 and H3K4me3, as being associated with Kleefstra syndrome 2 and autism spectrum disorder (ASD). However, the precise role of KMT2C mutations in brain disorders remains poorly understood. Here we employed CRISPR/Cas9 gene editing to analyze the effects of KMT2C brain specific knockout on animal behavior. Knocking out KMT2C expression in cortical neurons and the mouse brain resulted in decreased KMT2C levels. Importantly, KMT2C brain specific knockout animals exhibited repetitive behaviors, social deficits, and intellectual disability resembling ASD. Our findings shed light on the involvement of KMT2C in neurodevelopmental processes and establish a valuable model for elucidating the cellular and molecular mechanisms underlying KMT2C mutations and their relationship to Kleefstra syndrome 2 and ASD.